Teacher Strategies in Increasing Reading Interest of Grade 3 Students Through Literacy Activities at SDN Penjaringan 06 Pagi - Siti Afifah Fadhilah; Kasriman Kasriman (Journal of Educational Sciences, 2026)
Interest in reading is essential for developing students' literacy, creativity, and knowledge. Despite efforts to promote reading in Indonesia, interest remains low. Teachers' strategies play a crucial role in fostering reading interest. This study explores strategies used by teachers to boost reading interest among grade 3 students at SDN Penjaringan 06 Pagi through literacy activities. It aims to describe these strategies, identify influencing factors, and evaluate their effectiveness. Using a qualitative descriptive approach, research was conducted from January 2023 to May 2024. Data collection methods included observation, interviews, and documentation. Data validity was ensured through continuous observation, source triangulation, and method triangulation. Three teacher strategies were identified: (1) Direct Learning teachers guide students in listening and responding to reading; (2) Indirect Learning teachers act as facilitators and create a supportive environment; (3) Independent Learning students complete reading-related tasks at home or during school literacy time. Supporting factors include sufficient facilities and teacher preparation. Inhibiting factors involve intellectual, psychological, and environmental challenges, as well as students’ general disinterest in reading.